2008
DOI: 10.1177/021849230801600607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Perioperative Complications in Thoracic Surgery

Abstract: Obesity is perceived as a risk factor in general thoracic surgery. We conducted a single-center retrospective evaluation of perioperative complications in 822 patients who underwent thoracic surgery between 2000 and 2005. According to body mass index, 82 were underweight (< 18.5 kg m(-2)), 568 were normal (18.5-24.9 kg m(-2)), 155 were overweight (25.0-29.9 kg m(-2)), and 17 were obese (>or=30 kg m(-2)). A significant increase in preoperative comorbidity (hypertension and ischemic heart disease) was observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Diffi culty with intubation occasionally occurs with obese or extremely obese patients; however, normal-weight and underweight patients seemed to have fewer intraoperative problems than obese patients. 16,17 There was no statistical difference in postoperative cardiac complications among the four groups; however, thoracic complications clearly increased with a decreasing BMI. In particular, postoperative pneumonia was statistically higher in extremely underweight patients.…”
Section: Discussionmentioning
confidence: 82%
“…Diffi culty with intubation occasionally occurs with obese or extremely obese patients; however, normal-weight and underweight patients seemed to have fewer intraoperative problems than obese patients. 16,17 There was no statistical difference in postoperative cardiac complications among the four groups; however, thoracic complications clearly increased with a decreasing BMI. In particular, postoperative pneumonia was statistically higher in extremely underweight patients.…”
Section: Discussionmentioning
confidence: 82%
“…In a retrospective review of 499 patients who underwent resections for non-small cell lung cancer (NSCLC), a higher BMI was not associated with increased incidence of perioperative complications, mortality or length of stay (18). In contrast two retrospective studies have shown no effect on mortality but higher incidence of intra-thoracic complications (19, 20). …”
Section: Introductionmentioning
confidence: 81%
“…Moreover, prior studies of lung resection suggested that overweight and obesity had favorable surgical outcomes, whereas underweight adversely affected perioperative morbidity and operative mortality [ 7 , 12 ]. Conversely, in other studies of lung cancer, patients with elevated BMI had increased risk of intrathoracic [ 5 ] and respiratory complications [ 6 ]. Launer et al described on patients with lung cancer who underwent lobectomy, indicating that obesity was associated with increased risk of postoperative pulmonary complications, but not mortality or other morbidities after lobectomy [ 13 ].…”
Section: Introductionmentioning
confidence: 90%
“…Recently, attention has been focused on the factors influencing perioperative outcomes. One factor shown to predict outcomes in lung cancer is body mass index (BMI) [ 5 8 ]. However, to date, the data regarding the influence of elevated BMI on surgical outcomes have been mixed.…”
Section: Introductionmentioning
confidence: 99%